Students' representation based on high order thinking skills for the concept of light. (April 2020) - Fatmaryanti, S D; Ashari,; Wahidah, V S
Abstract: Light is one of the concepts in physics which is close with daily life. This descriptive study aims to explore student representations in terms of high order thinking skills (HOTS) on the concept of light. The research subjects were 30 students of junior high school in Purworejo. Data collection techniques using a test with three items in the form of descriptions based on indicators of HOTS. The data obtained were analysed qualitatively and the presentation of data analysis results through tables. The results showed that there are three forms of students' representation in understanding the concept of light, namely mathematics, picture and verbal representation. Image representation is the most commonly used concept of shadow while the concept of light propagation uses more verbal representation. The use of diverse representations in solving problems can facilitate the improvement of HOTS.